Study the cases of rupture uterus in a tertiary care teaching hospital, Jharkhand, India and its maternal and perinatal outcome - Beck, Rameshwari; Minj, Shashi Dinkar; Tirkey, Sarita; Kumar, Ajit; Sen, Sukanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Rupture of a pregnant uterus is a serious obstetric emergency and a common cause of maternal death. Study was done to evaluate the incidence, risk factors, management, maternal and fetal outcome of rupture uterus at RIMS. Methods: The present study was carried out in 80 cases of rupture uterus admitted in labour room in the department of Obstetrics and Gynaecology, RIMS, Ranchi, India from March 2014 to September 2015. Results: It was observed that the incidence rate of 0.763%. About 53.75% of ruptures of uterus were noted after 38 weeks of pregnancy. The cause of rupture uterus during labour in most of the cases was spontaneous (49.34%). scar rupture was the next frequent cause (45.33%) and traumatic rupture were 5.33%. Malpresentation and malposition contributed the most important aetiological factors causing spontaneous rupture during labour (43.24%). Hysterectomy was performed in 53.75% (subtotal, 32 cases i.e. 40% and total, 11 cases i.e. 13.75%). Conclusions: Rupture uterus is a serious and life threatening complication for both mother and the fetus. The leading cause of uterine rupture was found to be neglected and obstructed labor due to mismanagement by local untrained birth attendants. Timely recognition and referral to higher centers can reduce the maternal and fetal morbidity and mortality due to uterine rupture. Education and proper care especially of high risk patients like previous caesarean by competent personnel, proper use of oxytocin and early referral may help to reduce the incidence of rupture uterus.